Translation and cross-cultural validation of the Lithuanian version of the sleep-related breathing disorder scale of the Pediatric Sleep Questionnaire - Oboleviciene, Gintare; Miseviciene, Valdone (Frontiers in Pediatrics, 2025)
IntroductionSleep-disordered breathing (SDB) is considered the second most common chronic health condition in children. Untreated SDB is associated with long-term health consequences. Our objective was to translate the Pediatric Sleep Questionnaire (PSQ) into Lithuanian and culturally adapt and validate the translated version in order to improve the diagnosis of SDB in Lithuanian children.MethodsTranslations and cultural adaptations were performed to generate a Lithuanian version of the PSQ. Psychometric analysis was conducted on 112 Lithuanian children aged 2–17 years. All patients underwent overnight polysomnography.ResultsThe Lithuanian PSQ showed good internal consistency (Cronbach's alpha = 0.816). Lithuanian PSQ responses administered 14–30 days apart were strongly correlated (r = 0.924, p < 0.001, 95% CI 0.830–0.967). EFA of the Lithuanian PSQ confirmed four factors (“snoring”, “behavior”, “sleepiness”, and “other”). We found a sensitivity of 72.7% and specificity of 64.6% for a Lithuanian PSQ cutoff score of 8 to predict moderate-to-severe apnea, and a sensitivity of 85.0% and specificity of 62.0% to predict severe apnea. Using a Lithuanian PSQ cutoff ratio of 0.4, a sensitivity of 72.7% and specificity of 63.3% were found to predict moderate-to-severe apnea, and a sensitivity of 85.0% and specificity of 60.9% were found to predict severe apnea.ConclusionsThe Lithuanian version of the PSQ is a reliable, validated, and culturally adapted screening tool for the prediction of moderate-to-severe sleep apnea in children aged 2–17 years. However, polysomnography should be performed to confirm the diagnosis of sleep apnea and other SDB, and to determine the degree of the disorder and the need for treatment.